Perception of veterinary students about the use of euthanasia in companion animals in Lima, Peru - Rizo-Patrón, Alexandra (2021)
The aim of this study was to determine the perception of veterinary students from three universities in Lima, Peru, about the use of euthanasia in companion animals. For this, an information collection instrument was validated that included demographic variables of the respondent, questions about the use of euphemisms and acceptance of euthanasia in different settings, and proposals for the ethical assessment of euthanasia. In total, 640 surveys were collected, 65.5% corresponding to female students. All the students knew the term euthanasia, the euphemism "sleeping" being the most used as a student (63.3%) and the term euthanasia, properly speaking, the one they would use professionally (45.5%). Euthanasia was accepted mainly in case of chronic disease, both when it was about their own animal (83.3%) and in their future professional performance (83.1%). Besides, 68.6% of students mentioned having participated in at least one euthanasia of companion animals. The assessment of euthanasia as a "dignified death" had high acceptance (63.7%), as well as the majority rejection of the idea that euthanasia "devalues the veterinary medical profession" (73.3%). Animal suffering (87.9%) and their quality of life (62.7%) were the main considerations in deciding euthanasia. It is concluded that the perception of veterinary students towards euthanasia in companion animals was favourable, so it is necessary to reinforce professional training in medical, legal and ethical aspects that allow its adequate recommendation and application.